THE STUDENTS’ FACTOR DIFFICULTY IN READING ARTICLES IN THE JAKARTA POST NEWSPAPER - Nenni Triana Sinaga; Ermi Nuraini Parhusip; Chistina Natalina Saragih (J-Shelves of Indragiri (JSI), 2023)
This study examines the factors contributing to the learning difficulties encountered by second-semester English students after reading an article in the Jakarta Post. This study took a qualitative approach by employing questionnaires to collect data. The subject study was performed on 30 second-semester students. The study's findings indicate that factor difficulties were the difficulty in reading 35,9 %, 24,4%, not being confident (24.4%), 23,5% difficulty understanding, and 16,2% lack of vocabulary (16.2%). This research result recommends the lecturer of the reading subject as the reference for the material teaching. The lecturer knows this material is too difficult for second-semester students. Then, they will look for another strategy or idea to solve the student's difficulty learning to read.